Coupled dynamic simulation of wind turbine structures and tuned liquid dampers based on Adams - Bin-bin, Lang; Chen-xu, Wang; Chao-yu, Zhang; Hao-chen, Zhang; Xin-hui, Zhang; Xi-long, Ren (Journal of physics. Conference series, 2025)
This study establishes a structural-TLD coupled dynamic simulation model based on the coupled vibration theory of elastic structures-fluids and Adams’ virtual prototype technology. The model’s accuracy and applicability were validated by comparing it with previous experimental results. A dynamic response analysis was conducted on the influencing factors of TLD under complex loads, examining the effects of design parameters on vibration reduction, and providing recommendations for engineering. This serves as a reference for future TLD design, application, and the development of relevant standards.